2007
DOI: 10.1002/ar.20407
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the cerebral cortex of the humpback whale,Megaptera novaeangliae(Cetacea, Mysticeti, Balaenopteridae)

Abstract: Cetaceans diverged from terrestrial mammals between 50 and 60 million years ago and acquired, during their adaptation to a fully aquatic milieu, many derived features, including echolocation (in odontocetes), remarkable auditory and communicative abilities, as well as a complex social organization. Whereas brain structure has been documented in detail in some odontocetes, few reports exist on its organization in mysticetes. We studied the cerebral cortex of the humpback whale (Megaptera novaeangliae) in compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
176
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 226 publications
(194 citation statements)
references
References 94 publications
(210 reference statements)
17
176
1
Order By: Relevance
“…Studies of the marsupial cerebral cortex show that the visual regions flanking V1 are relatively thinner with a less prominent layer IV (Ashwell et al 2008), characteristics observed in carnivores and primates and, therefore, likely to be conserved in mammals and useful as a general rule for identifying V1. The cetacean visual cortex, located between the paralimbic cleft (medially) and the superior lateral sulcus (laterally), however, is derived with respect to terrestrial mammals and lacks a layer IV (Garey et al 1985;Hof and Van Der Gucht 2007; also see Furutani 2008 for a detailed report of cetacean V1 cytoarchitecture). The region of V1 sampled in all species was restricted to layers II-VI, since layer I was often poorly preserved in the older samples.…”
Section: Demarcation Of V1mentioning
confidence: 98%
See 1 more Smart Citation
“…Studies of the marsupial cerebral cortex show that the visual regions flanking V1 are relatively thinner with a less prominent layer IV (Ashwell et al 2008), characteristics observed in carnivores and primates and, therefore, likely to be conserved in mammals and useful as a general rule for identifying V1. The cetacean visual cortex, located between the paralimbic cleft (medially) and the superior lateral sulcus (laterally), however, is derived with respect to terrestrial mammals and lacks a layer IV (Garey et al 1985;Hof and Van Der Gucht 2007; also see Furutani 2008 for a detailed report of cetacean V1 cytoarchitecture). The region of V1 sampled in all species was restricted to layers II-VI, since layer I was often poorly preserved in the older samples.…”
Section: Demarcation Of V1mentioning
confidence: 98%
“…Variation among phylogenetic groups in the cellular density of cortical columns and in the morphology and biochemistry of neuronal phenotypes have been reported in rodents (Celio 1990;Beaulieu 1993;Skoglund et al 1996), bats and Eulipotyphla (Valverde 1986), cetaceans (Garey et al 1985;Haug 1987;Hof et al 1992;Hof and Van der Gucht 2007;Butti et al 2009), carnivores (Peters and Yilmaz 1993), and primates (Zilles et al 1986;Peters and Sethares 1991;Preuss and Goldman-Rakic 1991a, c;Hof and Morrison 1995;Hof et al 2000Hof et al , 2001Hof and Sherwood 2005). Further studies have reported differentiated expressions of calcium-binding proteins in different taxa Preuss and Kaas 1996;del Rio and DeFelipe 1997;Hof et al 1999;Preuss 2001), qualitative and quantitative differences in cortical projection layers in primates (Preuss 2001), species-specific quantities of von Economo neurons (Nimchinsky et al 1995(Nimchinsky et al , 1999Butti et al 2009;Hakeem et al 2009;Allman et al 2010), and diverse cellular scaling relationships in different mammalian orders (Herculano-Houzel et al 2007;Azevedo et al 2009;Sherwood et al 2009;Herculano-Houzel 2010;Gabi et al 2010).…”
Section: Introductionmentioning
confidence: 98%
“…Whales have one unusual feature; that is, they are considered as one of the most intelligent animals since their brain has some common spindle cells similar to the human brain [27]. Due to the presence of these spindle cells, we humans became distinct creatures of the world as these are responsible for the decision, feelings, and community behaviour.…”
Section: Whale Optimization Algorithmmentioning
confidence: 99%
“…This perspective influenced later thinking about cetacean brains and led to the “initial brain” hypothesis of cetacean neocortical evolution [20] that asserted cetacean neocortex was primitive. However, modern neuroanatomical techniques convincingly demonstrate that the cetacean neocortex has a degree of regional parcellation comparable to that of many terrestrial mammals (see Box 1) [21,22]. There is certainly no evidence that the “cetacean scheme” is incapable of supporting complex processing similar to that in primates and other mammals.…”
Section: Contemporary Cetacean Neuroanatomymentioning
confidence: 99%